(untitled) (Interdisciplinary Studies Journal, 2025)
Prolonged hospitalization in the Intensive Care Unit (ICU) can lead to physical and emotional impairments characteristic of Post-Intensive Care Syndrome (PICS). In this context, it is essential to investigate the consequences of PICS and its impact on patient functionality, assisting healthcare professionals in preventing hospital readmission through. A total of 24 adult survivors of prolonged ICU stays were evaluated, categorized by discharge time, sex, and age group. A significant difference was observed in discharge time (p=0.001) and percentage of goal achievement (p=0.011). Additionally, the "Emotional Problems" domain and handgrip strength showed sex-related differences, with higher values in men (p=0.046). When comparing older and younger adults, younger adults performed better in age, six-minute walk test distance (p=0.007), and handgrip strength (p=0.007). This study highlights the importance of post-discharge rehabilitation and the challenges of PICS, emphasizing the need for further research and protocols to improve patient recovery.